2010
DOI: 10.1111/j.1468-3083.2010.03853.x
|View full text |Cite
|
Sign up to set email alerts
|

Axillary basal cell carcinoma: additional 25 patients and considerations

Abstract: Axillary Basal cell carcinomas are rare. No particular predisposing or risk factor is recorded. They do not seem to be significantly more aggressive than other basal cell carcinomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
2
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 23 publications
0
3
2
1
Order By: Relevance
“…Previous studies have shown that the incidence rate of axillary BCC varies between 0.15% and 0.43% of total BCCs . In contrast, this rate in the present study was revealed to be 1.8%.…”
Section: Clinical and Histologic Features Of 6 Cases With Axillary Bacontrasting
confidence: 97%
See 2 more Smart Citations
“…Previous studies have shown that the incidence rate of axillary BCC varies between 0.15% and 0.43% of total BCCs . In contrast, this rate in the present study was revealed to be 1.8%.…”
Section: Clinical and Histologic Features Of 6 Cases With Axillary Bacontrasting
confidence: 97%
“…Those differences may be relevant to the lifestyle, job (outdoors or in‐house), climate, and recreational habits (sports, leisure, tanning), as well as skin types. In a previous series of 25 cases of axillary BCC, the ratio of males to females was 3 : 2 . In contrast, our cases were all females.…”
Section: Clinical and Histologic Features Of 6 Cases With Axillary Bacontrasting
confidence: 58%
See 1 more Smart Citation
“…Strickland and colleagues postulated that ultraviolet radiation at distant sun-exposed sites may lead to a suppression of immune surveillance that in turn allows BCCs to develop in sun-protected sites [ 39 ]. Many have endorsed this theory as contributing to the formation of BCCs in other covered sites, such as the genital regions [ 40 ] and the axilla [ 25 - 26 , 41 ]. Other researchers have suggested that local alterations in cell matrix interactions lead to changes in skin texture, shape, and tension that may contribute to tumor formation in sun-protected areas [ 42 ].…”
Section: Reviewmentioning
confidence: 99%
“…O principal fator de risco associado ao desenvolvimento do CBC é a exposição à radiação ultravioleta. Outras circunstâncias envolvidas com a sua etiologia são: predisposição genética (síndrome do nevo basocelular, síndrome de Bazex e xeroderma pigmentoso) 28 , exposição ao arsênico, fatores ambientais (hidrocarbonetos e pesticidas), imunossupressão, injúrias (queimadura e trauma), exposição à radiação ionizante 29 , fototipo baixo (cabelo, olhos e pele clara), sexo masculino, nevo sebáceo 30 , idade avançada, exposição solar e queimaduras na infância 31,32,33 .…”
Section: Etiologiaunclassified